DYNAMICS OF DEVELOPMENT AND EVALUATION OF AGILITY IN SCHOOL EDUCATION (1st-12th GRADE) - Milena Tarnichkova; Marina Petrova (Scientific Publishing House. NSA Press, 2020)
Physical activity is an important criterion for a healthy lifestyle and a prerequisite for improving the motor abilities of adolescents. The aim of this study is to establish the level of development of physical quality agility in all stages of school education. In order to fulfill the set aim of the research, we used sports-pedagogical testing. The research was carried out with 232 pupils from 1st to 12th grade. We used variation analysis and comparative analysis with t-criterion of Student for independent samples to process the study results. Following the dynamics of the development of the studied indicator between the different classes, we report a positive increase six times, and a decrease in the result - three times (from 2nd to 3rd grade; from 7th to 8th grade and from 10th to 11th grade). Between grades 5th - 6th and 8th - 9th there was no increase in the results. The average number of points reported for each class ranged between 9 and 13 points, which according to the evaluation table means a "GOOD" assessment of agility development. Our study shows that the dynamics of the mean level of the researched indicator in the age aspect changes regressively, with the values decreasing from 1st to 12th grade. Comparing the changes in the mean values of pupils divided by class and gender, we established that, overall, boys are faster than girls when performing the test.